Analysis of Patients Visiting Niigata University Medical and Dental Hospital with Chief Complaints of Metal Allergy and/or Focal Infection in the Previous 8 Years - Yosuke Akiba; Ken Tomizuka; Masaru Kaku; Maiko Kawasaki; Masako Nagasawa; Ryohei Takano; Katsumi Uoshima (The Indonesian Journal of Dental Research, 2011)
Dental metal allergy and dental focal infection are possible causes of dermatological diseases, but have been the subjects of few reports to date. We have been treating such patients in our special clinic for more than 20 years.The purpose of the present study was to investigate the mouths of patients visiting our dental hospital over an 8-year period, with the aim of clarifying whether dental metal allergy and/or dental focal infection affects their dermatologic conditions.We surveyed all clinical records of the 185 patients who visited Niigata University Medical and Dental Hospital with chief complaints of dental metal allergy since 2002. Diagnostics of skin diseases, periodontal records, periapical lesions, dental caries, dental metal series patch test results and Electron Probed Micro-Analysis (EPMA) data were investigated. Ninety-two (49%) patients were suffering from pustulosis palmaris et plantaris and 20 (11%) patients had lichen planus. Eighty-two (49%) patients showed positive reactions on patch testing. Based on the result of patch tests, Ni showed the highest positivity rate (62%, 51 patients), but on EPMA, the number of patients with Ni as an allergen was 14 (27%). On the other hand, more than 98% of patients who showed positive reactions on patch test to Pd and Au had these metals in their dental prostheses. In addition, 112 (60%) patients showed the possibility of dental focal infections